The role of student activists in strengthening nationalist characters in the industrial revolution 4.0 era - Farid Fadillah; Suharno Suharno (Jurnal Civics: Media Kajian Kewarganegaraan, 2021)
This study aims to (1) identify roles, (2) describe the challenges and (3) the efforts of BEM UNY activist students in strengthening the nationalist character in the era of the industrial revolution 4.0. This type of research is descriptive with a qualitative approach. The data collection techniques of this research were interviews and documentation. The subjects of this study were seven student activists from BEM UNY for the period 2020 who were determined by purposive technique. This research data analysis using qualitative analysis which consists of data collection, data reduction, data presentation, and conclusions. The results of this study are as follows. (1) Student activists from BEM UNY play a role in strengthening the nationalist character in the era of the industrial revolution 4.0, as agents of change, social control, iron stocks. (2) The challenges faced are the "ups and downs" of enthusiasm within oneself, participation in every activity, adaptation of technological sophistication, and people who have radical views. (3) Efforts are made, namely creating attractive work programs by integrating technological sophistication, creating movements or communities as alternatives, adapting, making oneself a good example, and taking a personal approach.